Innovation and optimization in autoimmune encephalitis trials: the design and rationale for the Phase 3, randomized study of satralizumab in patients with NMDAR-IgG-antibody-positive or LGI1-IgG-antibody-positive autoimmune encephalitis (CIELO) - Lee, Soon-Tae; Abboud, Hesham; Irani, Sarosh R.; Nakajima, Hideto; Piquet, Amanda L.; Pittock, Sean J.; Yeh, E. Ann; Wang, Jiawei; Rajan, Sharmila; Overell, James; Smith, Jillian; St Lambert, Jane; et al. (Frontiers in Neurology, 2024)
Background Autoimmune encephalitis (AIE) encompasses a spectrum of rare autoimmune-mediated neurological disorders, which are characterized by brain inflammation and dysfunction. Autoantibodies targeting the N-methyl-d-aspartic acid receptor (NMDAR) and leucine-rich glioma-inactivated 1 (LGI1) are the most common subtypes of antibody-positive AIE. Currently, there are no approved therapies for AIE. Interleukin-6 (IL-6) signaling plays a role in the pathophysiology of AIE. Satralizumab, a humanized, monoclonal recycling antibody that specifically targets the IL-6 receptor and inhibits IL-6 signaling, has demonstrated efficacy and safety in another autoantibody-mediated neuroinflammatory disease, aquaporin-4 immunoglobulin G antibody-positive neuromyelitis optica spectrum disorder, and has the potential to be an evidence-based disease modifying treatment in AIE. Objectives CIELO will evaluate the efficacy, safety, pharmacodynamics, and pharmacokinetics of satralizumab compared with placebo in patients with NMDAR-immunoglobulin G antibody-positive (IgG+) or LGI1-IgG+ AIE. Study design CIELO (NCT05503264) is a prospective, Phase 3, randomized, double-blind, multicenter, basket study that will enroll approximately 152 participants with NMDAR-IgG+ or LGI1-IgG+ AIE. Prior to enrollment, participants will have received acute first-line therapy. Part 1 of the study will consist of a 52-week primary treatment period, where participants will receive subcutaneous placebo or satralizumab at Weeks 0, 2, 4, and every 4 weeks thereafter. Participants may continue to receive background immunosuppressive therapy, symptomatic treatment, and rescue therapy throughout the study. Following Part 1, participants can enter an optional extension period (Part 2) to continue the randomized, double-blind study drug, start open-label satralizumab, or stop study treatment and continue with follow-up assessments. Endpoints The primary efficacy endpoint is the proportion of participants with a ≥1-point improvement in the modified Rankin Scale (mRS) score from study baseline and no use of rescue therapy at Week 24. Secondary efficacy assessments include mRS, Clinical Assessment Scale of Autoimmune Encephalitis (CASE), time to rescue therapy, sustained seizure cessation and no rescue therapy, Montreal Cognitive Assessment, and Rey Auditory Verbal Learning Test (RAVLT) measures. Safety, pharmacokinetics, pharmacodynamics, exploratory efficacy, and biomarker endpoints will be captured. Conclusion The innovative basket study design of CIELO offers the opportunity to yield prospective, robust evidence, which may contribute to the development of evidence-based treatment recommendations for satralizumab in AIE.